Electronic structure, optical and structural properties of organic 5,5 '-Dibromo-2,2 '-bithiophene - Kurban, Mustafa; Gündüz, Bayram (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2018)
The changes in the electronic, optical and structural properties of the title compound have been investigated using experimental and theoretical techniques. The semi-emprical relations have been proposed for the calculation of the refractive index (n) from its measured and calculated energy gap (E-g) data. The simulated IR and Raman spectra characteristics and HOMO-LUMO energies, harmonic frequencies, Mulliken atomic charges, radial distribution functions (RDFs) and coordination number of binary interactions were recorded with the aid of density functional theory (DFT) based on optimized structure for different solvent environments. Ultraviolet-visible (UV-vis) spectral analysis has been carried out using experimental techniques and time-dependent (TD) DFT calculations. Furthermore, the effects of the concentrations on the optoelectronic properties were experimentally investigated. The measured and calculated results are discussed to get an insight for the future optoelectronic applications. (C) 2018 Elsevier GmbH. All rights reserved.
Keywords: Organic molecules; UV-vis spectroscopy; Electronic structure; Refractive index; DFT